PEMBATALAN GUGATAN ULTRA PETITA OLEH PENGADILAN TINGGI BALIKPAPAN DALAM PERKARA PERCERAIAN ANTARA RAFEGE ZEBUA DENGAN CYNTHIA VERONICA OEIYONO DI P.N. BALIKPAPAN (Studi Kasus Putusan Pengadilan Tinggi Kalimantan Timur Nomor 125/Pdt/2019/PTSMR) - Devi Haryanto; Stanislaus Atalim (Jurnal Hukum Adigama, 2021)
Decisions of judges in the civil sector apply the principle of iudex non ultra petita or ultra petita non cognoscitur or the judge only determines what is submitted and proven by the applicants or plaintiffs. The problem in this research is how the cancellation of the ultra petita lawsuit by the Balikpapan High Court in the divorce case between Rafege Zebua and Cynthia Veronica Oeiyono at the Balikpapan District Court? The results showed that the cancellation of the ultra petita lawsuit by the Balikpapan High Court in the divorce case between Rafege Zebua and Cynthia Veronica Oeiyono at the Balikpapan District Court was not in accordance with the facts of the trial. This is because Cynthia Veronica Oeiyono as the Plaintiff requested ex aequo et bono, so the Balikpapan District Court Judge's decision was not included in the ultra petita category, because the judge only completed what was demanded in his primary petitum. Balikpapan District Court judges also only carry out the mandate stipulated in Article 40 of Law Number 23 of 2006 conceming Population Administration, namely efforts to create legal certainty for divorce between the Plaintiff and Defendant through reporting by the concemed to record court decisions regarding divorce to the Population Office and Palembang City Civil Registry and Balikpapan City Population and Civil Registry Office to issue a Divorce Certificate